FUZZY MODELING OF TOOL WEAR IN DRILLING - Sivarao, Subramonian (2005)
Machining operations confronted by a shortage of technical manpower and pricing competition, not only need to implement automated and operator-free technology, but also to meet the demands for much higher performance of products, higher reliability, longer life and miniaturization. Tool wear has a large influence on the economics of the machining operations. Hence, tool wear sensing should be one of the primary objectives in order to produce the required end products in an automated industry, so that, a new tool may be introduced at the instant at which the existing tool has worn out. Thus preventing any hazards occurring to the machine or deterioration of the surface finish. Often, tool wear affects the surface texture seriously and changes the tool geometry. This paper discusses a specific approach of surface modeling and approximation of tool wear in drilling based on cutting force analysis by fuzzy system.